2000
DOI: 10.2165/00002018-200023020-00006
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Factors that Could Affect Adverse Drug Reaction Reporting According to Hospital Pharmacists in Great Britain

Abstract: ADR training and meetings would be a useful step in improving hospital pharmacist ADR reporting. Therefore, we recommend that the CSM and the RPSGB liaise with regional drug information centres and schools of pharmacy to provide more study days and training programmes for hospital pharmacists. Furthermore, the CSM should write to the 'Drugs and Therapeutics Committee' of each hospital and encourage them to develop a written local policy for pharmacist ADR reporting. Further studies should be conducted to test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
120
3
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(150 citation statements)
references
References 8 publications
25
120
3
2
Order By: Relevance
“…The initial draft of the survey questionnaire was developed using information from the literature about ADR reporting among healthcare professionals [19][20][21][22][23] as well as the findings of our previous qualitative study, which involved interviews with community pharmacists.…”
Section: Methodsmentioning
confidence: 99%
“…The initial draft of the survey questionnaire was developed using information from the literature about ADR reporting among healthcare professionals [19][20][21][22][23] as well as the findings of our previous qualitative study, which involved interviews with community pharmacists.…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7] Failure to report ADEs is influenced by many factors, such as lack of time, indifference, malpractice litigation concerns, lack of motivation, lack of economic incentive, complacency, lack of knowledge on ADE reporting requirements, and negative attitudes. 5,6,8,9 In addition, reluctance to send reports based on mere suspicion of ADEs, lack of confidence in recognizing adverse drug reactions, misconceptions about ADE reporting, and difficulty in accessing means of reporting (eg, forms) [10][11][12][13][14][15][16] also affect the reporting of ADEs. ADE reporting is also hampered by healthcare professionals' attitudes toward reporting 17 and possibly by personal characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Previous studies reported a strong association between adverse drug reactions reporting and knowledge, attitude and practice of the healthcare professionals. 6,14,13,15 Therefore to establish and improve Pharmacovigilance program in any country, improving the knowledge, attitude and practice of health professional is essential. 16,13 Community Pharmacists (CPs) as part of their pharmaceutical care functions have roles and professional responsibilities to monitor the safety of medicines for which they are sole custodians.…”
mentioning
confidence: 99%